PERLINDUNGAN HUKUM UNTUK TENAGA KERJA YANG DIRUMAHKAN BERDASARKAN UNDANG-UNDANG-UNDANG NO 11 TAHUN 2020 TENTANG CIPTA KERJA - I Komang Gede Budiarta (Fakultas Hukum Universitas Dwijendra, 2021)
Abstract Based on data from the Ministry of Manpower (Kemnaker) from April 7, 2020, as a result of the Covid-19 pandemic, there were 39,977 companies in the formal sector that chose to lay off their workers and lay off their workers. Of the 39,977 companies, a total of 1,010,579 workers were affected by this. In detail, 873,090 workers from 17,224 companies were laid off, while 137,489 workers were laid off from 22,753 companies. Based on the background, the author formulates the problem, namely What is the status of the laid-off workforce based on Law Number 11 of 2020 concerning Job Creation? What is the form of legal protection for laid-off workers based on Law Number 11 of 2020 concerning Job Creation? The research method used in this study is a normative legal research method in which normative legal research is a legal research conducted by examining library materials or secondary data. using normative case studies. Workers who are laid off still have status as workers and are bound by a working relationship with the company, so they are still entitled to their rights as workers, including the matter of wages where wage arrangements have been regulated in Article 88A paragraph (1) of Law Number 11 of 2020 concerning Job Creation so that if it is not regulated in a work agreement, company regulation, or collective labor agreement, then the laid-off workforce is still domiciled as the company's workforce so that they still get their rights as workers, one of which is the work wage. Legal protection for laid-off workers can fight for their rights through industrial relations dispute settlement mechanisms. In addition, if workers who have been laid off either because of resigning or for other reasons regulated in Law Number 11 of 2020 concerning Job Creation, the workforce also retains their rights as workers, whether they are entitled to severance pay and/or awards. the period of service and compensation that should have been received, without discriminating based on the reason for the layoff.